Impacts of microcystin, a cyanobacterial toxin, on laboratory rodents in vivo - Andrea Ziková; Radovan Kopp (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2008)
Cyanobacterial water blooms became a global problem/issue because beside a dramatic deterioration of water quality parameters they also produce cyanobacterial toxins being harmful for animals and humans. Cyanotoxins especially the most prominent one, microcystin-LR (MC-LR), are of major concern and they have been reported to cause even death of mammals following ingestion or ingurgitation due to hepatotoxic modes of action. The aim of the recent study is to summarize briefly the impacts of microcystin on laboratory rodents, mice and rats, being used as models for other mammals including human beings. Most experimental approaches used intraperitoneal rather than oral and intratracheal application of microcystins, especially MC-LR, being the most efficient way to induce adverse impacts on different target organs. However, no matter how the exposure of rodents was performed, microcystins induced severe harmful impacts on the different target organs, preferentially the liver, for instances hemorrhages and apoptosis in liver, liver tumours, adverse effects on gut, kidney, testis and epididymis including spermatogenesis, on lung, on serum parameters and on progeny. In addition to these histological findings, microcystin was found to affect specifically biochemical parameters of target organs such as enzymes e.g. GST, CAT, GR, GPX, SOD, AST, ALT, γ-GT, protein phosphatases, SDH, SoDH and LDH or stress proteins such as HSP-70 and further parameters such as hepatic sulfhydryl content, GSH depletion, total bilirubin, urea nitrogen, and creatinine. Gene array analyses revealed that microcystin affects genes related to actin organization, cell cycle, apoptosis, cellular redox potential, cell signalling, albumin metabolism, glucose homeostasis pathway and organic anion transport polypeptide system. In combination with a further proteomics approach the proteomic analyses indicate that liver apoptosis induced by microcystin can be induced by two pathways: the BID-BAX-BCL2 and the reactive oxygen species pathway. The reviewed data clearly show that microcystin, especially MC-LR is able to cause severe adverse impacts on laboratory rodents and therefore there is an emerging need for further research to cover the major concern about cyanobacterial water blooms affecting mammals including human beings.